The Sino-Peruvian relation and the construction of the official narrative of Peru as a hub management - A. Guerra-Barón (Ибероамериканские тетради)
This article discusses the driving forces behind the establishment of diplomatic relations between China and Peru. Accordingly, the importance of bilateral cooperation in the development of Sino-Peruvian relations is being assessed. Given that the Chinese presence in Peru is an extended phenomenon, the article attempts to determine the extent of China’s influence on bilateral relations and its importance in building the official narrative of Peruvian decision-makers regarding the trans-Pacific image they aim to project in relation to China. For this reassion the article recurs to the productive notion of power, focusing on intangible elements mainly to enquire by the discursive constructions of the Peruvian technocrat agents and related practices embedded into the Sino-Peruvian relation −strongly led by the Asian country. The article concludes that the main topics of bilateral cooperation make it possible to single out four stages of China’s international policy towards Peru. Even though the Sino-Peruvian relation does not ground either can be explained exclusively on economic criteria or an institutional basis, the current associativity between both countries answer to the reciprocal knowledge triggered by migratory waves of the Chinese in moments of economic and political stress. At the same time, the discourses and narratives created by Peruvian technocrats acknowledge the country’s trans-Pacific identity; China’s weight in this identification is defining for the narrative of Peru as a bridge country in the 1990s and South America’s operational hub in Asia in the 21st century.